Cadherin-11 regulates protrusive activity in Xenopus cranial neural crest cells upstream of Trio and the small GTPases - Kashef, Jubin (Cold Spring Harbor Laboratory Press, 2009)
Xenopus Cadherin-11 (Xcad-11) is expressed when cranial neural crest cells (CNC) acquire motility. However, its function in stimulating cell migration is poorly understood. Here, we demonstrate that Xcad-11 initiates filopodia and lamellipodia formation, which is essential for CNC to populate pharyngeal pouches. We identified the cytoplasmic tail of Xcad-11 as both necessary and sufficient for proper CNC migration as long as it was linked to the plasma membrane. Our results showing that guanine nucleotide exchange factor (GEF)-Trio binds to Xcad-11 and can functionally substitute for it like constitutively active forms of RhoA, Rac, and cdc42 unravel a novel cadherin function.